32 Emotional lability in hippocampal atrophy due to autoimmune limbic encephalitis. (28th May 2019) - Argyropoulos, Georgios PD; Moore, Lauren; Loane, Clare; Roca-Fernandez, Adriana; Lage-Martinez, Carmen; Butler, Christopher R
Abstract : Objective/Aims: Autoimmune limbic encephalitis (LE) is commonly associated with cognitive and psychiatric disturbances at the acute stage of the disease, and with residual episodic memory impairment. While behavioural and psychiatric symptoms generally dissipate post-acutely, very little is known about the profile of persistent neuropsychiatric symptoms. In particular, emotional lability represents an elusive entity that may be misdiagnosed as a manifestation of comorbid mood or personality change and can have disabling consequences, due to the stigma attached to the loss of emotional control. We aimed to assess the post-acute profile of emotional lability and its neuroanatomical correlates in LE. Methods: We analysed acute neuroradiological reports, clinical notes, scores on post-acute neuropsychological tests and self-administered questionnaires on mood, emotion, and affect (including the Centre for Neurologic Study-Lability Scale; CNS-LS), along with structural MRI and resting-state fMRI datasets in relation to emotional lability in a large cohort of patients (n=36) that had received a neurological diagnosis of LE, presented with focal hippocampal structural abnormalities in the acute phase, and post-acute hippocampal atrophy and thalamic volume reduction. Results: Emotional lability was present in 50% of the patients. It was associated with increased tearfulness compared with non-labile patients and healthy controls, whereas no patient presented with labile laughter (CNS-LS). Patients with emotional lability (n=18) did not differ from those without (n=18) in any demographic or clinical details in their acute or post-acute presentation (autoantibodies, immunosuppressive therapy, seizures, antidepressant medication, age at or delay from symptom onset), or in residual depression, anxiety, impulsiveness, memory impairment, or executive dysfunction, or in hippocampal and thalamic volumes. Instead, the presence and extent of emotional lability across patients was associated with reduced resting-state hemodynamic activity in and hippocampal functional connectivity with regions in the inferior and superior parietal lobules. Conclusions: We present the first investigation of persistent affective dysregulation in LE. Emotional lability is common following LE, but is not a manifestation of depression, anxiety, impulsiveness, or executive dysfunction. The type of emotional lability seen in LE is semiologically distinct from pseudobulbar affect observed in other neurological diseases. While LE is characterised by focal hippocampal atrophy, functional abnormalities in regions interacting with the hippocampus may provide a more parsimonious explanation of emotional lability than the volume of medial temporal lobe structures. Functional abnormalities in parietal regions supporting perspective taking and social-affective processing may compromise patients' emotion regulation.